Multiletramentos, hipertextos e práticas textuais em curso de formação continuada na EAD - Beserra , Elaine Anjos dos Santos (2024)
This research discusses the contribution of hypertext multiliteracies to the formation of active designer students regarding text in a Distance Education Specialization course. It aims to understand if the textual practices integrated into the Moodle virtual learning environment of the Specialization course in Education in Digital Culture, Distance Learning modality, at UEFS, contributed to the formation of active designer students regarding text. For this study, activities posted on the VLE by the teacher of the ECD002 component - TDIC Applied to Education were chosen as corpora, as well as responses to two online questionnaires and the meanings of one of the activities carried out by the component students. Theoretically, the research is based on studies on multiliteracies, hypertexts, and textual practices in Distance Education. Methodologically, it is based on a qualitative study, with a method for interpreting information and design analysis, using Moodle interfaces and two online questionnaires as devices for information construction, one sociodemographic questionnaire applied to 128 students by the teacher of the ECD001 component - Introduction to Distance Education, during the synchronous class of that component, and another questionnaire developed for this research, available in the VLE of the ECD002 component, in September 2023. The research results showed that the activities available in the component, through the Moodle platform, presented multiliterate textual genres characteristic of this interface. Furthermore, due to the hypertextual nature of the platform, it was possible for students to expand the dialogue with texts of various languages and modalities of materialization, although this contact did not always expand the way of signifying these texts in the resolution of activities by the students, in the sense of making them active designers regarding the texts.